A FORMAÇÃO CONTINUADA DE PROFESSORES DA REDE MUNICIPAL DE SÃO LUÍS E A ORGANIZAÇÃO DO ENSINO EM CICLOS: uma Unidade de Educação Básica em foco - MARTINS, Ana Paula de Albuquerque (2014)
This study presents a reflection on the Continued Education of teachers and teaching organized in cycles in a Teaching Unit Basic Municipal of Sao Luis. Its main objective was to investigate the impact of existing continued education school for the development of pedagogical practices of teachers in teaching organized in cycles. The survey was conducted on a qualitative approach, using content analysis procedures. Document analysis and semistructured interviews were used for its design. The theoretical context of the continuing training of teachers received contributions from authors such as LIMA (2001); GATTI (2003); BARBIERI, CARVALHO E UHLE (1995); ALARCÃO (1998); FUSARI E RIOS (1995); MARIN (1995); FREITAS (1999, 2002, 2007) and for the analysis of teaching organized in cycles MAINARDES (2001 , 2005, 2007 , 2009) ; MITRULIS e BARRETO (1999, 2001 ) ; FREITAS ( 2002a , 2002b , 2003) , among others. It is concluded from the study, continued education in the country has been characterized by an immediate compensatory and design, embodied in actions and streamlined and surface courses , often in distance mode, need more in depth discussion on the continuing education as an instrument of professionalization and the school as a site for development . Might also conclude that the Basic Education Unit searched the school is considered as a priority site for continuing education and has its organization and development centered on the figure of pedagogical coordinator, however, the material conditions, the design and the methodology applied in actions existing continuing education at the school have had an unsatisfactory impact in terms of development of the pedagogical practices of teachers in teaching organized in cycles .